2013
DOI: 10.1029/2012gm001313
|View full text |Cite
|
Sign up to set email alerts
|

Colorado Student Space Weather Experiment: Differential Flux Measurements of Energetic Particles in a Highly Inclined Low Earth Orbit

Abstract: The Colorado Student Space Weather Experiment (CSSWE) is a three-unit (10 cm  10 cm  30 cm) CubeSat mission funded by the National Science Foundation; it was launched into a low Earth, polar orbit on 13 September 2012 as a secondary payload under NASA's Educational Launch of Nanosatellites program. The science objectives of CSSWE are to investigate the relationship of the location, magnitude, and frequency of solar flares to the timing, duration, and energy spectrum of solar energetic particles reaching Eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 31 publications
(29 reference statements)
1
35
0
Order By: Relevance
“…The Colorado Student Space Weather Experiment (CSSWE: http://lasp.colorado.edu/home/csswe/) is a three‐unit (10 cm × 10 cm × 30 cm) CubeSat mission funded by the National Science Foundation, launched into a low‐altitude, highly inclined orbit on 13 September 2012 as a secondary payload under NASA's Educational Launch of Nanosatellites program [ Li et al ., , , ]. CSSWE contains a single science payload, the Relativistic Electron and Proton Telescope integrated little experiment (REPTile).…”
Section: Csswe Mission and Instrument Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Colorado Student Space Weather Experiment (CSSWE: http://lasp.colorado.edu/home/csswe/) is a three‐unit (10 cm × 10 cm × 30 cm) CubeSat mission funded by the National Science Foundation, launched into a low‐altitude, highly inclined orbit on 13 September 2012 as a secondary payload under NASA's Educational Launch of Nanosatellites program [ Li et al ., , , ]. CSSWE contains a single science payload, the Relativistic Electron and Proton Telescope integrated little experiment (REPTile).…”
Section: Csswe Mission and Instrument Descriptionsmentioning
confidence: 99%
“…REPTile uses the depth of penetration of the particle into the detector stack to infer the energy of incoming particles. Particles must also have adequate energy to penetrate through a thin beryllium foil to reach the first detector [ Li et al ., ], and then the particle species is determined based on the energy deposited in each detector. Particles depositing 0.25 < E < 1.5 MeV are classified as electrons, and those depositing E > 4.5 MeV as protons.…”
Section: Csswe Mission and Instrument Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is called cosmic ray albedo neutron decay, or CRAND. Recently, relativistic electrons near the inner edge of the inner radiation belt were measured by the Colorado Student Space Weather Experiment CubeSat (Li et al, 2012 and identified as CRANDproduced . CRAND was identified as an important source for the inner proton radiation belt six decades ago (Kellogg, 1959;Selesnick et al, 2014;Singer, 1958), but not as a significant source of trapped electrons (Lenchek et al, 1961;Walt & Farley, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Funding for CSSWE was received in January 2010 for $840k from the NSF. CSSWE's primary science objective is to study space weather in Earth's magnetosphere [1]. The science payload, the Relativistic Electron and Proton Telescope integrated little experiment (REPTile) [2], is a miniaturized version of the Relativistic Electron and Proton Telescope (REPT) [3] on board NASA's Van Allen Probes mission [4].…”
Section: Introductionmentioning
confidence: 99%